IoT Based Smart Cupboard Design - Trio Atmojo; Shazan Dhiya; Indah Sulistyowati; Arief Wicaksono (Universitas Muhammadiyah Sidoarjo, 2021)
During the rainy season, the clothes can dry for 1 day or more. Often times when on the way home from work or school it is trapped in rain so that the clothes used are little damp, because the clothes are still used for tomorrow so the clothes are not possible to wash and can dry overnight. easy to open or break into by anyone, given the habit of people used to storing valuables in the cupboard, an extra security system is needed. Then a IOT-Based Smart Cupboard Design is made which aims to improve the function of a conventional wardrobe to be multifunctional, which is equipped with a damp clothes dryer feature and is equipped with a Fingerprint sensor which can only be accessed by the owner to open the wardrobe. to be equipped with a Fingerprint, which functions as extra security in opening cabinets where valuables are usually found. Also equipped with a fan and heater incubator functions in drying damp clothes. This tool is equipped with an IoT which functions as an On Off control for the fan and an incubator heater in heating damp clothes.